Consequences of Electrolyte Degradation for the Electrochemical Performance of Li1+x(NiaCobMn1-a-b)1-xO2. Issue 13 (7th August 2015) - Peng, H.-J.; Urbonaite, S.; Villevieille, C.; Wolf, H.; Leitner, K.; Novák, P.
Abstract : In lithium-ion batteries, the stability of the electrolyte during cycling is among the key parameters that govern cycle life and specific-charge retention. For the case of carbonate-based electrolytes, one of the main reduction products is the alkoxide anion. Here, we report a study of the parameters influencing the formation of these anions during cycling and of the effects that this process has on cycling performance. To this end, conventional and overlithiated lithium-nickel-cobalt-manganese-oxide cathodes were studied in combination with an electrolyte containing ethyl methyl carbonate. The extent of trans-esterification reaction within the electrolyte, serving as an indicator for the alkoxide-anion formation, was estimated based on gas-chromatography results. An analysis of the electrolyte extracted from cells after testing them at different cycling rates revealed a crucial role of anode passivation in the process of alkoxide-anion formation. The upper cutoff potential was found to be inversely proportional to the extent of trans-esterification. Further analysis of the electrolyte extracted from the full-cells containing Li1.05 (Ni0.33 Co0.33 Mn0.33 )0.95 O2 suggested that electrolyte instability toward the anode can cause a surface layer buildup on the cathode side, which in turn deteriorates the overall cell performance.